Design Expert Supported Mathematical Optimization and Predictability Study of Buccoadhesive Pharmaceutical Wafers of Loratadine - Chakraborty, Prithviraj (Hindawi Publishing Corporation, 2013)
Objective. The objective of this work encompasses the application of the response surface approach in the development of buccoadhesive pharmaceutical wafers of Loratadine (LOR). Methods. Experiments were performed according to a 3(2) factorial design to evaluate the effects of buccoadhesive polymer, sodium alginate (A), and lactose monohydrate as ingredient, of hydrophilic matrix former (B) on the bioadhesive force, disintegration time, percent (%) swelling index, and time taken for 70% drug release (t (70%)). The effect of the two independent variables on the response variables was studied by response surface plots and contour plots generated by the Design-Expert software. The desirability function was used to optimize the response variables. Results. The compatibility between LOR and the wafer excipients was confirmed by differential scanning calorimetry, FTIR spectroscopy, and X-ray diffraction (XRD) analysis. Bioadhesion force, measured with TAXT2i texture analyzer, showed that the wafers had a good bioadhesive property which could be advantageous for retaining the drug into the buccal cavity. Conclusion. The observed responses taken were in agreement with the experimental values, and Loratadine wafers were produced with less experimental trials, and a patient compliant product was achieved with the concept of formulation by design.